Partnership dissolution in Austria during multiple crises, 2018-2023 - Isabella Buber-Ennser; Caroline Berghammer; Maria Winkler-Dworak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2024)
At the onset of the COVID-19 pandemic in 2020, divorce rates across European countries significantly declined and remained low through 2023. This sustained low level is notable, especially given the potential for a rebound in postponed divorces. This study examines partnership dissolution in Austria from 2018 to 2023, covering the pandemic and a subsequent period of high inflation. It specifically investigates the role of socioeconomic and family characteristics. The analysis draws on 24 quarterly waves from the Austrian Labour Force Surveys, focusing on cohabiting and married couples aged 20 to 54 (n=32,913 couples). Households participated in five consecutive quarters. Changes in partnership status across waves were analysed using random effects logistic panel regression models. The dissolution of partnerships sharply declined during the pandemic (2020-22) and remained at a lower level throughout the period of high inflation (2022-23). The risk of separation decreased most significantly in two groups: couples without children (compared to those with children, especially two or more) and couples with low to medium education levels. We interpret the less pronounced decline in dissolution risk among parents as an indication of greater strain, particularly due to work-family conflicts. Additionally, the reduced rate of union dissolutions among low- and medium-educated couples likely reflects financial challenges in setting up a second household, exacerbated by inflation and rising living costs. The economic barriers to partnership dissolution may be considered a social problem.
Keywords: 300; Separation; union dissolution; divorce; COVID-19; pandemic; inflation; Austria